2020
DOI: 10.7150/thno.37200
|View full text |Cite
|
Sign up to set email alerts
|

ASIC1a induces synovial inflammation via the Ca2+/NFATc3/ RANTES pathway

Abstract: Rationale: Synovial inflammation is one of the main pathological features of rheumatoid arthritis (RA) and is a key factor leading to the progression of RA. Understanding the regulatory mechanism of synovial inflammation is crucial for the treatment of RA. Acid-sensing ion channel 1a (ASIC1a) is an H+-gated cation channel that promotes the progression of RA, but the role of ASIC1a in synovial inflammation is unclear. This study aimed to investigate whether ASIC1a is involved in the synovial inflammation and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 90 publications
(86 reference statements)
1
32
0
Order By: Relevance
“…In the past 2 years, our research team has shown that activated ASIC1a induces autophagy, synovial invasion, and synovial inflammation by mediating calcium influx (Gao, Xu, Ge, & Chen, 2019; Niu et al, 2020; Zhang et al, 2020). Calpains are ubiquitous calcium‐activated cysteine proteases.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 2 years, our research team has shown that activated ASIC1a induces autophagy, synovial invasion, and synovial inflammation by mediating calcium influx (Gao, Xu, Ge, & Chen, 2019; Niu et al, 2020; Zhang et al, 2020). Calpains are ubiquitous calcium‐activated cysteine proteases.…”
Section: Introductionmentioning
confidence: 99%
“…In a study, a reduction in pH was detected in the synovial fluid of AA rats, and ASIC1a was upregulated in AA rat articular chondrocytes in vivo ( 4 ). Further studies have indicated that the expression level of ASIC1a is increased in the synovial tissues of AA rats than in normal rats, suggesting that ASIC1a may be involved in the pathological process of RA ( 18 , 19 ).…”
Section: Potential Therapeutic Targets Of Asic1a In Rheumatoid Arthrimentioning
confidence: 99%
“…In a previous study, we found that ASIC1a, ASIC2a, and ASIC3 were expressed in the articular chondrocytes of rats with AA, and that the expression levels of ASIC1awere significantly higher than those of other subunits ( 4 ). More recently, it has been reported that the expression of ASIC1a is significantly increased in human RA synovial tissues, primary human RASF, and the ankle synovium of AA rats ( 18 , 19 ). Table 1 summarizes the tissue and cell distribution of ASIC1a.…”
Section: Basic Biological Characteristics Of Asic1amentioning
confidence: 99%
See 2 more Smart Citations